2022
DOI: 10.3389/fimmu.2022.991743
|View full text |Cite
|
Sign up to set email alerts
|

Target organ expression and biomarker characterization of chemokine CCL21 in systemic sclerosis associated pulmonary arterial hypertension

Abstract: IntroductionSystemic sclerosis (SSc) is a heterogenous disorder that appears to result from interplay between vascular pathologies, tissue fibrosis and immune processes, with evidence for deregulation of chemokines, which normally control immune trafficking. We recently identified altered levels of chemokine CCL21 in SSc associated pulmonary arterial hypertension (PAH). Here, we aimed to define target organ expression and biomarker characteristics of CCL21.Materials and methodsTo investigate target organ expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Moreover, CCL21 concentrations positively correlated with PAH development and the occurrence of PAH-related events, suggesting that this chemokine might be a promising marker for predicting the risk of SSc-related PAH and PAH progression [ 178 ]. CCL21 association with SSc-PAH and its predictive value of PAH development were recently confirmed by the same research group in two new independent cohorts [ 179 ].…”
Section: Cytokinesmentioning
confidence: 79%
“…Moreover, CCL21 concentrations positively correlated with PAH development and the occurrence of PAH-related events, suggesting that this chemokine might be a promising marker for predicting the risk of SSc-related PAH and PAH progression [ 178 ]. CCL21 association with SSc-PAH and its predictive value of PAH development were recently confirmed by the same research group in two new independent cohorts [ 179 ].…”
Section: Cytokinesmentioning
confidence: 79%
“…In a cohort of SSc patients, C-C motif ligand 20 (CCL20) levels correlated directly with the mPAP values measured by RHC; a positive correlation was also found between CCL20 levels and the presence of primary biliary cholangitis [ 152 ], indicating a common pathogenesis between this rare manifestation and PAH in SSc. Moreover, the CCL21 serum levels were found to be elevated in the serum and lung tissue of patients with SSc-PAH [ 153 , 154 ].…”
Section: Inflammationmentioning
confidence: 99%
“…Recent studies have shown how vast and ever-expanding the field of biomarkers is in SSc. Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
“…Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Cytokeratin 17 (CK17), marginal zone protein B1 (MZB1), and leucine-rich α2-glycoprotein-1 (LRG1) appear to be potential biomarkers for SSc, with CK17 negatively associated with disease severity and higher values of CK17 protective [37,[59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation